2014
DOI: 10.1089/scd.2013.0388
|View full text |Cite
|
Sign up to set email alerts
|

Murine Cardiosphere-Derived Cells Are Impaired by Age but Not by Cardiac Dystrophic Dysfunction

Abstract: To be clinically relevant as a therapy for heart failure, endogenous progenitor cells must be isolated and expanded from aged and/or diseased tissue. Here, we investigated the effect of age and cardiac impairment resulting from lack of dystrophin on murine cardiosphere-derived cells (CDCs). CDCs were isolated and expanded from atrial biopsies from wild-type mice aged 1.5, 6, 18, and 24 months and from mdx mice aged 6 and 18 months. Cardiac function was measured in mdx mice and age-matched wild-type mice using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 54 publications
0
16
2
Order By: Relevance
“…Several reports have demonstrated that c-kit positive cardiac stem cells from aged mice and patients underwent senescence 10 11 . CDCs from aged mice also have shown senescent phenotype and decreased cell proliferation, expression of stem cell markers and differentiation 12 . However, the influence of aging on cardiac stem cells is not fully understood.…”
mentioning
confidence: 99%
“…Several reports have demonstrated that c-kit positive cardiac stem cells from aged mice and patients underwent senescence 10 11 . CDCs from aged mice also have shown senescent phenotype and decreased cell proliferation, expression of stem cell markers and differentiation 12 . However, the influence of aging on cardiac stem cells is not fully understood.…”
mentioning
confidence: 99%
“…No differences were noticed in the differentiation potential of CDCs from chow‐fed and HFD‐fed mice, that further confirms the conclusion that the high‐fat diet does not affect cardiac progenitor cells. In a recent study, we showed that CDCs isolated from mice aged 6 and 18 months had the same number and regenerative potential, whether from dystrophic mice, with mild cardiac impairment, or from age‐matched wild‐type mice [39]. The differentiation of ADMSCs increased expression levels of cardiac genes; however, ADMSCs from HFD‐fed mice seemed to have a slower response to the induction of differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, senescent CPC, which have lost their telomerase activity because of aging, may give rise to structurally old cardiomyocytes destined to become less functional, with severely depressed mechanical performance and a marked tendency to apoptosis, along with the manifestation of an aging cardiac phenotype (Kajstura et al, ). Cardiosphere‐derived cells (CDC) isolated from aged mice showed a decline in the expression of CDC stem markers, such as c‐kit and Sca‐1, together with reduction of their clonogenic potential, suggesting failure of regenerative potential with age (Hsiao et al, ).…”
Section: Cardiac Progenitor Cells and Agingmentioning
confidence: 99%